Industrial Policy of the European Union: Institutional Preconditions for Formation and Features of Realization - Tsyplitska Olena O.; Ianenkova Iryna G. (Problemi Ekonomiki, 2018)
The aim of the article is to determine the socio-economic, political and institutional prerequisites for the formation of EU industrial policy and the specifics of its implementation. It is determined that industrial policy is one of the main priorities of the economic development of EU countries and the key focus of the Europe 2020 strategy. EU industrial policy was formed under the influence of the growing competition in the world market, the need to realize the idea of uniting European countries with a view to ensuring the stability of the political situation. Deepening the democratic foundations of government, expanding the rights and freedoms of citizens, the need for convergence of economic development with increasing number of members of the community have become new challenges for the formation of a single internal market and ensuring the competitiveness of EU industrial enterprises. As a result, the developed model of industrial policy has focused on supporting a favorable environment for the development of small and medium-sized businesses, developing and implementing innovative technologies, creating equal opportunities in a competitive environment (horizontal industrial policy) as opposed to sectoral policies and reducing state support for individual industries, ensuring the implementation of framework agreements. The most successful practices of using the model of EU industrial policy, aimed at creating favorable conditions to increase the competitiveness of industrial enterprises, can be used to elaborate Ukraine’s industrial development strategy.